Identification of nicotine-seeking and avoiding larval zebrafish using a new three-choice behavioral assay - Schneider, Henning; Pearson, Anna; Harris, Drew; Krause, Sabrina; Tucker, Andrew; Gardner, Kaitlyn; Chinyanya, Kuzivakwashe (Frontiers in Molecular Neuroscience, 2023)
Nicotine dependence is one of the main causes of preventable diseases in the United States. Nicotine-seeking and avoidance behavioral assays in larval zebrafish could be used for identifying potential new pharmacotherapeutics in an early phase of drug discovery and could facilitate the identification of genes and genomic variations associated with nicotine-seeking and avoidance behavior. A new three-choice behavioral assay has been developed for the identification of nicotine-seeking and avoiding larval zebrafish. The three choices are represented by three compartments of a gradient maze. Video-recording and subsequent quantitative analysis of the swimming track using EthovisionXT (Noldus) resulted in the identification of three behavioral phenotypes. Nicotine-seeking larval zebrafish occupied nicotine compartments for longer periods and entered the nicotine-containing compartments most frequently. Nicotine-avoiders spent most of the cumulative time in the water compartment or entered the water compartment most frequently. Non-seekers remained in the center compartment for most of the time. In the gradient maze, about 20 - 30% of larval zebrafish had a preference for low nicotine concentrations whereas nicotine avoidance was stronger at higher nicotine concentrations. Lower concentrations of nicotine (0.63μM, 6.3 μM) resulted in higher percentages of nicotine seekers whereas high nicotine concentrations (63 μM, 630 µM) resulted in higher percentages of nicotine avoiders. Pre-treatment of larval zebrafish with nicotine slightly increased the percentage of nicotine avoiders at lower nicotine concentrations. Treatment with varenicline strongly increased the percentage of nicotine avoiders at lower nicotine concentrations. The results show that larval zebrafish have individual preferences for nicotine that could change with drug treatment. The three-choice gradient maze assay for larval zebrafish provides a new testing paradigm for studying the molecular and cellular mechanisms of nicotine action and the discovery of potential new pharmacotherapeutics for the treatment of smoking cessation.